St. Thomas Aquinas on punishing souls - Toner, Patrick (International journal for philosophy of religion, 2012)
The details of St. Thomas Aquinas’s anthropological view are subject to debate. Some philosophers believe he held that human persons survive their deaths. Other philosophers think he held that human persons cease to exist at their death, but come back into being at the general resurrection. In this paper, I defend the latter view against one of the most significant objections it faces, namely, that it entails that God punishes and rewards separated souls for the sins or merits of something else: the (non-existent) persons to whom those souls once belonged. The objector takes this entailment to be problematic. I argue that it fits in well with St. Thomas’s views about punishment and about persons.